Interventions to reduce harm from continued tobacco use. - Lindson-Hawley, N; Hartmann-Boyce, J; Fanshawe, T; Begh, R; Farley, A; Lancaster, T (Cochrane Collaboration, 2016)
BACKGROUND: Although smoking cessation is currently the only guaranteed way to reduce the harm caused by tobacco smoking, a reasonable secondary tobacco control approach may be to try and reduce the harm from continued tobacco use amongst smokers unable or unwilling to quit. Possible approaches to reduce the exposure to toxins from smoking include reducing the amount of tobacco used, and using less toxic products, such as pharmaceutical, nicotine and potential reduced-exposure tobacco products (PREPs), as an alternative to cigarettes. OBJECTIVES: To assess the effects of interventions intended to reduce the harm to health of continued tobacco use, we considered the following specific questions: do interventions intended to reduce harm have an effect on long-term health status?; do they lead to a reduction in the number of cigarettes smoked?; do they have an effect on smoking abstinence?; do they have an effect on biomarkers of tobacco exposure?; and do they have an effect on biomarkers of damage caused by tobacco? SEARCH METHODS: We searched the Cochrane Tobacco Addiction Group Trials Register (CRS) on the 21st October 2015, using free-text and MeSH terms for harm reduction, smoking reduction and cigarette reduction. SELECTION CRITERIA: Randomized or quasi-randomized controlled trials of interventions to reduce the amount smoked, or to reduce harm from smoking by means other than cessation. We include studies carried out in smokers with no immediate desire to quit all tobacco use. Primary outcomes were change in cigarette consumption, smoking cessation and any markers of damage or benefit to health, measured at least six months from the start of the intervention. DATA COLLECTION AND ANALYSIS: We assessed study eligibility for inclusion using standard Cochrane methods. We pooled trials with similar interventions and outcomes (> 50% reduction in cigarettes a day (CPD) and long-term smoking abstinence), using fixed-effect models. Where it was not possible to meta-analyse data, we summarized findings narratively. MAIN RESULTS: Twenty-four trials evaluated interventions to help those who smoke to cut down the amount smoked or to replace their regular cigarettes with PREPs, compared to placebo, brief intervention, or a comparison intervention. None of these trials directly tested whether harm reduction strategies reduced the harms to health caused by smoking. Most trials (14/24) tested nicotine replacement therapy (NRT) as an intervention to assist reduction. In a pooled analysis of eight trials, NRT significantly increased the likelihood of reducing CPD by at least 50% for people using nicotine gum or inhaler or a choice of product compared to placebo (risk ratio (RR) 1.75, 95% confidence interval (CI) 1.44 to 2.13; 3081 participants). Where average changes from baseline were compared for different measures, carbon monoxide (CO) and cotinine generally showed smaller reductions than CPD. Use of NRT versus placebo also significantly increased the likelihood of ultimately quitting smoking (RR 1.87, 95% CI 1.43 to 2.44; 8 trials, 3081 participants; quality of the evidence: low). Two trials comparing NRT and behavioural support to brief advice found a significant effect on reduction, but no significant effect on cessation. We found one trial investigating each of the following harm reduction intervention aids: bupropion, varenicline, electronic cigarettes, snus, plus another of nicotine patches to facilitate temporary abstinence. The evidence for all five intervention types was therefore imprecise, and it is unclear whether or not these aids increase the likelihood of smoking reduction or cessation. Two trials investigating two different types of behavioural advice and instructions on reducing CPD also provided imprecise evidence. Therefore, the evidence base for this comparison is inadequate to support the use of these types of behavioural advice to reduce smoking. Four studies of PREPs (cigarettes with reduced levels of tar, carbon and nicotine, and in one case delivered using an electronically-heated cigarette smoking system) showed some reduction in exposure to some toxicants, but it is unclear whether this would substantially alter the risk of harm. We judged the included studies to be generally at a low or unclear risk of bias; however, there were some ratings of high risk, due to a lack of blinding and the potential for detection bias. Using the GRADE system, we rated the overall quality of the evidence for our cessation outcomes as 'low' or 'very low', due to imprecision and indirectness. A 'low' grade means that further research is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate. A 'very low' grade means we are very uncertain about the estimate. AUTHORS' CONCLUSIONS: People who do not wish to quit can be helped to cut down the number of cigarettes they smoke and to quit smoking in the long term, using NRT, despite original intentions not to do so. However, we rated the evidence contributing to the cessation outcome for NRT as 'low' by GRADE standards. There is a lack of evidence to support the use of other harm reduction aids to reduce the harm caused by continued tobacco smoking. This could simply be due to the lack of high-quality studies (our confidence in cessation outcomes for these aids is rated 'low' or 'very low' due to imprecision by GRADE standards), meaning that we may have missed a worthwhile effect, or due to a lack of effect on reduction or quit rates. It is therefore important that more high-quality RCTs are conducted, and that these also measure the long-term health effects of treatments.